Removal of extracellular Toxoplasma gondii tachyzoites from suspended cell culture. Issue 5 (October 2016) - Baba, Minami; Kitoh, Katsuya; Takashima, Yasuhiro
Abstract: Tachyzoites of Toxoplasma gondii, an obligate intracellular parasite, actively invade a broad spectrum of cell types. T. gondii infects leukocytes and spreads to distant organs such as the brain, lungs and muscles. However, the mechanism of T. gondii transmission from infected leukocytes to peripheral organs is unknown. To show the dynamics of infected leukocytes and intracellular parasites in vivo, previous studies have prepared T. gondii -infected leukocytes and injected them into circulation in experimental animals. However, when the infected leukocytes are prepared in vitro, some extracellular tachyzoites remain in the leukocyte cell culture because it is almost impossible to wash out these extracellular tachyzoites. These extracellular tachyzoites may distort experimental results. In this study, we report a method for removing extracellular tachyzoites from leukocyte culture suspension using antibody-conjugated magnetic beads. Using this method, extracellular tachyzoites in suspension cell culture can be effectively eliminated. Graphical abstract: Highlights: Extracellular parasites could be removed by polyclonal antibody-conjugated beads. A mouse anti-TgSAG1 monoclonal antibody was also available. Repeated treatment using the beads was more effective.